The Ideal Roman Daughter through the Life Course: Three Case Studies - Lamond, Emily A. (My University, 2015)
The following thesis is a collection of three case studies which shed light on the ideal roles of a daughter in the Roman family over the course of her life. Plentiful recent scholarship on children in the Roman world exists, but few scholars have focused exclusively on girls and women qua daughters. The case studies are centred on epistolary sources which span the late Republic to the second century CE. The chapters of this thesis concern Timoxena, the two-year-old daughter of Plutarch; Minicia Marcella, the teenage daughter of Fundanus; and Tullia, the adult daughter of Cicero. These case studies will illustrate primarily that adult behaviours were constantly idealized throughout the life course of a daughter, but the expectations for a daughter did change to accommodate the actual age of the daughter concerned. In addition, the ideal behaviours expected of a daughter did not necessarily become more gendered as she grew older and became a full member of society, but her contribution to the bond of reciprocal obligation with her parents, dictated by pietas, was expected to intensify as she matured.
Keywords: Roman social history, history of the family, Roman women